2022
DOI: 10.2166/wst.2022.043
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the performance and mechanism of magnetic Ni0.5Cu0.5Fe2O4 in activating peroxydisulfate for ciprofloxacin degradation

Abstract: Magnetic nickel-copper ferrite (NixCuyFe2O4) nano-catalyst was synthesized by co-precipitation method, and it exhibited excellent ability for activating peroxydisulfate (PDS) in the degradation of ciprofloxacin (CIP). As-prepared Ni0.5Cu0.5Fe2O4 properties were characterized by Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscope equipped with an energy-dispersive X-ray (SEM-EDX), transmissions electron microscopy (TEM), N2 adsorption-desorption isotherm plot of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Based on these results, it was concluded that the decreased activity of the catalyst was not mainly caused by metal leaching but attributed to the presence of oxidation products adsorbed on the catalyst surface, which could not be removed completely by washing. These species occupied some sites on the catalyst surface and acted as competitors during the oxidation process (Wang et al 2022), consuming the oxidant and leading to declined removal efficiency of RhB in the consecutive runs.…”
Section: Catalytic Oxidation Of Organic Pollutantsmentioning
confidence: 99%
“…Based on these results, it was concluded that the decreased activity of the catalyst was not mainly caused by metal leaching but attributed to the presence of oxidation products adsorbed on the catalyst surface, which could not be removed completely by washing. These species occupied some sites on the catalyst surface and acted as competitors during the oxidation process (Wang et al 2022), consuming the oxidant and leading to declined removal efficiency of RhB in the consecutive runs.…”
Section: Catalytic Oxidation Of Organic Pollutantsmentioning
confidence: 99%
“…Furthermore, NiCu ferrites possess desirable characteristics such as high electrical resistivity, low eddy currents, and low hysteresis loss, which make them suitable candidates for use in transformers and surface mount devices (SMDs) [10]. In addition, Cu 0.5 Ni 0.5 Fe 2 O 4 ferrite has been used for biomedical applications [11] and also as a reusability catalyst for the removal of organic pollution from aquatic environments [12]. Dat et al [9] have successfully synthesized a nanocomposite comprised of reduced graphene oxide, Cu 0.5 Ni 0.5 Fe 2 O 4 nanoparticles, and polyaniline (RGO-CNF-PANI).…”
Section: Introductionmentioning
confidence: 99%